Implementasi Pertanggungjawaban Pidana Korporasi: Analisis Efektivitas Pasal 20 UU Pemberantasan Tindak Pidana Korupsi - Ismaidar Ismaidar; Muhamad Ilham (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study critically examines the implementation of Article 20 of Law No. 31/1999, as amended by Law No. 20/2001, concerning the eradication of corruption (UU Tipikor), with a focus on corporate accountability in corruption offenses. It aims to address three primary concerns: (1) the practical application of corporate liability mechanisms, (2) the effectiveness of sanctions imposed on corporations, and (3) the legal obstacles that impede the full enforcement of corporate criminal responsibility. Employing a normative legal approach, this research integrates statutory analysis, case law evaluation, and theoretical exploration. The findings highlight considerable challenges in proving corporate liability, as well as the limited scope and effectiveness of current penalties. These difficulties stem from ambiguities in distinguishing between the responsibilities of individuals and the corporation, and the lack of consistent legal interpretation by law enforcement authorities. The study proposes a set of recommendations, including the formulation of clear technical guidelines, the continuous professional development of legal practitioners, the enhancement of sanctions against corporations, and the establishment of a centralized database of judicial decisions involving corporate criminal liability. These measures are essential to ensure more effective corporate accountability and the prevention of systemic corruption in Indonesia.